Positive pole piece, battery and preparation method of positive pole piece

By setting up a dry preparation process with a three-layer composite structure on the positive electrode sheet, the problems of difficult electrolyte absorption and decreased conductivity in the dry electrode preparation process are solved, efficient lithium ion transmission and improved electrochemical performance are achieved, and production costs and environmental pollution are reduced.

CN120690803APending Publication Date: 2025-09-23ZHUHAI KECHUANG LITHIUM BATTERY TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510707225.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-29
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

In the existing dry electrode preparation process, the electrode has difficulty absorbing the electrolyte, the electrode conductivity decreases, and the active material cannot be fully utilized, which affects the electrochemical performance of the lithium-ion battery. In addition, the traditional wet process uses organic solvents, which causes environmental pollution and high production costs.

Method used

The positive electrode plate adopts a three-layer composite structure, including the first composite layer, the second composite layer and the third composite layer, which respectively contain conductive agents and binders of different compositions. Through fiberization treatment and rolling technology, shallow diffusion is carried out between the layers during the preparation process to improve the bonding strength and ion transmission efficiency, and avoid the use of organic solvents.

Benefits of technology

It improves the kinetic performance of the positive electrode and the energy density of the battery, reduces the risk of lithium plating, improves the cycle performance and safety of the battery, and reduces the production cost, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120690803A_ABST
    Figure CN120690803A_ABST
Patent Text Reader

Abstract

The invention provides a positive pole piece, a battery and a preparation method of the positive pole piece. The positive pole piece comprises a positive current collector and a composite layer arranged on the surface of at least one side of the positive current collector, the composite layer comprises a first composite layer, a second composite layer and a third composite layer which are sequentially arranged along the thickness direction of the positive pole piece, and the first composite layer is arranged on the surface of the positive current collector; the first composite layer comprises a first conductive agent and a first binder, the second composite layer comprises a positive electrode active material, a second conductive agent, a second binder and a first fast ion conductor, and the third composite layer comprises a third conductive agent, a third binder and a second fast ion conductor. According to the invention, the electrochemical performance of the battery prepared by a dry-method electrode preparation process can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a positive electrode sheet, a battery and a preparation method thereof. Background Art

[0002] In the manufacturing process of lithium-ion batteries, the traditional wet electrode preparation process has always dominated. The wet electrode preparation process dissolves the active material, conductive agent and binder in a solvent to form a uniform slurry, which is then coated on the metal current collector. After drying and compaction, the electrode is prepared. However, the wet electrode preparation process usually requires the use of a large amount of organic solvents, such as NMP (N-methylpyrrolidone). These organic solvents have volatility and toxicity problems, posing potential hazards to worker health and the environment. In addition, the wet electrode preparation process consumes a large amount of organic solvents during the preparation process and consumes a lot of energy during the drying process, which increases the production cost of lithium batteries.

[0003] The core of the dry electrode preparation process is to eliminate the use of organic solvents, avoiding solvent contamination and complex solvent recovery issues in the wet electrode preparation process, and can effectively solve the problems existing in the wet electrode preparation process. However, in the existing technology, in order to improve the energy density of lithium-ion batteries, the surface density of the electrode is usually designed to be relatively large, and the requirements for the compaction density of the electrode are relatively high. As a result, the electrode produced using the dry electrode preparation process has difficulty absorbing electrolyte, the electrode conductivity is reduced, and the active material cannot be fully utilized, which affects the electrochemical performance of the lithium-ion battery. Summary of the Invention

[0004] The present invention aims to solve the above-mentioned defects of the prior art and provides a positive electrode sheet, a battery and a preparation method thereof, so as to effectively improve the electrochemical performance of the battery prepared by the dry electrode preparation process.

[0005] To solve the above problems, the first aspect of the present invention provides a positive electrode sheet, comprising: a positive electrode current collector and a composite layer provided on at least one side surface of the positive electrode current collector;

[0006] The composite layer includes a first composite layer, a second composite layer and a third composite layer sequentially arranged along the thickness direction of the positive electrode sheet, wherein the first composite layer is arranged on the surface of the positive electrode current collector;

[0007] The first composite layer includes a first conductive agent and a first binder, the second composite layer includes a positive electrode active material, a second conductive agent, a second binder and a first fast ion conductor, and the third composite layer includes a third conductive agent, a third binder and a second fast ion conductor.

[0008] A second aspect of the present invention provides a method for preparing a positive electrode sheet, for preparing the positive electrode sheet as described in the first aspect, the preparation method comprising the following steps:

[0009] The first conductive agent and the first binder are mixed and then subjected to a fiberization treatment to prepare a first composite layer;

[0010] Mixing a positive electrode active material, a first fast ion conductor, and a second conductive agent to prepare a first mixture, adding a second binder to the first mixture to prepare a second mixture, and performing a fiberization treatment on the second mixture to prepare a second composite layer;

[0011] mixing the second fast ion conductor and the third conductive agent to obtain a third mixture, adding a third binder to the third mixture to obtain a fourth mixture, and performing a fiberization treatment on the fourth mixture to obtain a third composite layer;

[0012] The first composite layer, the second composite layer and the third composite layer are stacked in sequence and roll-pressed to obtain a composite layer;

[0013] The composite layer is arranged on at least one side surface of a positive electrode current collector, the first composite layer is in contact with the positive electrode current collector, and roll pressing is performed to obtain a positive electrode sheet.

[0014] A third aspect of the present invention provides a battery, comprising the positive electrode sheet as described in the first aspect, or a positive electrode sheet prepared by the method for preparing the positive electrode sheet as described in the second aspect.

[0015] The positive electrode sheet of the present invention is achieved by arranging a first composite layer, a second composite layer and a third composite layer on the surface of the positive electrode current collector. The first composite layer is arranged on the surface of the positive electrode current collector and is in direct contact with the positive electrode current collector. The first composite layer increases the content of the first conductive agent and the first binder, which can effectively increase the bonding strength between the positive electrode current collector and the composite layer, and also promote the electron transfer between the positive electrode current collector and the composite layer, which is beneficial to reducing the polarization of the positive electrode sheet; the second composite layer is arranged on the surface of the first composite layer. The second composite layer serves as the main energy storage layer in the composite layer, and includes both a positive electrode active material that can store and release lithium ions and a first fast ion conductor. The first fast ion conductor can achieve efficient transmission of lithium ions and improve electrical conductivity. At the same time, the first fast ion conductor and the positive electrode active material are located in the same layer, which can It can achieve efficient combination and separation of electrons and lithium ions, which is beneficial to further reduce the resistance of the positive electrode sheet, effectively improving the kinetic performance of the positive electrode sheet and the energy density of the battery; the third composite layer is arranged on the surface of the second composite layer, and the third composite layer is arranged close to the battery diaphragm. The second fast ion conductor in the third composite layer can directly contact the electrolyte, which can improve the lithium ion transmission performance of the positive electrode sheet, promote ion exchange between the electrolyte and the positive electrode active material, reduce the lithium ion concentration on the surface of the positive electrode sheet during high current charging, and effectively reduce the risk of lithium plating. The third composite layer is arranged above the second composite layer, avoiding direct contact between the electrolyte and the positive electrode active material in the second composite layer, effectively reducing the dissolution of transition metals in the positive electrode active material in the high-voltage section, which is beneficial to improving the cycle performance and energy density of the battery. In this embodiment, through the mutual cooperation between the first composite layer, the second composite layer and the third composite layer, the ultra-high specific capacity of the positive electrode sheet as a whole is guaranteed, and the rapid transmission of lithium ions can be achieved, which is beneficial to improving the electrochemical performance of the battery.

[0016] The method for preparing the positive electrode sheet of the present invention, by sequentially preparing the first composite layer, the second composite layer, and the third composite layer, can avoid the mutual influence of the composite layers during the preparation process, and can ensure the uniformity of the mixing of the various mixed materials, thereby improving the performance of each composite layer. After each composite layer is prepared separately, the first composite layer, the second composite layer, and the third composite layer are combined together, which can cause shallow diffusion on the contact surface of each composite layer, which is beneficial to improving the bonding strength between each composite layer, and is beneficial to improving the structural strength of the composite layer and the ion and electron transmission efficiency between each composite layer. The preparation method of this embodiment is conducive to further improving the electrochemical performance of the battery. The preparation method adopts a dry preparation process, avoids the use of organic solvents, is environmentally friendly, can reduce production costs, and is suitable for industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A schematic structural diagram of a positive electrode sheet provided in an embodiment of the present invention;

[0018] Figure 2 A process flow chart for preparing a positive electrode sheet according to an embodiment of the present invention. DETAILED DESCRIPTION

[0019] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0020] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0021] In addition, the terms "comprising", "including", "containing", and "having" are not restrictive, and other steps and other components that do not affect the results can be added. Unless otherwise specified, materials, equipment, and reagents are commercially available.

[0022] In addition, although the present invention describes the various steps in the preparation in the form of S210, S220 and S230, this description is only for ease of understanding. The form of S210, S220 and S230 does not limit the order of the steps.

[0023] In order to solve the above technical problems, the first aspect of the embodiment of the present application provides a positive electrode plate, combined with Figure 1 As shown, the positive electrode sheet includes: a positive electrode current collector 10 and a composite layer 20 provided on at least one side of the positive electrode current collector 10; the composite layer 20 includes a first composite layer 21, a second composite layer 22 and a third composite layer 23 sequentially provided along the thickness direction of the positive electrode sheet, and the first composite layer 21 is provided on the surface of the positive electrode current collector 10;

[0024] The first composite layer 21 includes a first conductive agent and a first binder, the second composite layer 22 includes a positive electrode active material, a second conductive agent, a second binder and a first fast ion conductor, and the third composite layer 23 includes a third conductive agent, a third binder and a second fast ion conductor.

[0025] The positive electrode sheet provided in this embodiment is provided with a first composite layer, a second composite layer and a third composite layer on the surface of the positive electrode current collector. The first composite layer is provided on the surface of the positive electrode current collector and is in direct contact with the positive electrode current collector. The first composite layer increases the content of the first conductive agent and the first binder, which can effectively increase the bonding strength between the positive electrode current collector and the composite layer, and can also promote electron transfer between the positive electrode current collector and the composite layer, which is beneficial to reducing the polarization of the positive electrode sheet; the second composite layer is provided on the surface of the first composite layer. The second composite layer serves as the main energy storage layer in the composite layer, and includes both a positive electrode active material capable of storing and releasing lithium ions and a first fast ion conductor. The first fast ion conductor can achieve efficient transmission of lithium ions and improve electrical conductivity. At the same time, the first fast ion conductor and the positive electrode active material are located in the same layer. It can achieve efficient combination and separation of electrons and lithium ions, which is beneficial to further reduce the resistance of the positive electrode sheet, effectively improving the kinetic performance of the positive electrode sheet and the energy density of the battery; the third composite layer is arranged on the surface of the second composite layer, and the third composite layer is arranged close to the battery diaphragm. The second fast ion conductor in the third composite layer can directly contact the electrolyte, which can improve the lithium ion transmission performance of the positive electrode sheet, promote ion exchange between the electrolyte and the positive electrode active material, reduce the lithium ion concentration on the surface of the positive electrode sheet during high current charging, and effectively reduce the risk of lithium plating. The third composite layer is arranged above the second composite layer, avoiding direct contact between the electrolyte and the positive electrode active material in the second composite layer, effectively reducing the dissolution of transition metals in the positive electrode active material in the high-voltage section, which is beneficial to improving the cycle performance and energy density of the battery. In this embodiment, through the mutual cooperation between the first composite layer, the second composite layer and the third composite layer, the ultra-high specific capacity of the positive electrode sheet as a whole is guaranteed, and the rapid transmission of lithium ions can be achieved, which is beneficial to improving the electrochemical performance of the battery.

[0026] Fast ion conductors are a type of solid material with high ionic conductivity. They have a special crystal structure and can be regarded as consisting of two sublattices: one is a rigid sublattice formed by non-moving ions, and the other is a liquid sublattice composed of moving ions. In this structure, the number of positions that can be occupied by moving ions in the rigid sublattice is much greater than the number of moving ions, and these positions are interconnected to form ion diffusion channels. Lithium ions can move freely in these channels, thereby achieving high ionic conductivity. Based on the above embodiment, as an optional implementation method, the first fast ion conductor and the second fast ion conductor are the same or different and are independently selected from Li3SBF4, LiAlSiO4, LiTaSiO5, Li 10 Si2PO 10 and Li2P3SiO8 or a combination thereof. Therefore, the above-mentioned fast ion conductors have good ionic conductivity, which is conducive to improving the efficient transmission of lithium ions in the positive electrode sheet.

[0027] Based on the above embodiment, as an optional embodiment, the content of the first fast ion conductor in the second composite layer 22 is lower than the content of the second fast ion conductor in the third composite layer 23. Therefore, the content of the second fast ion conductor in the third composite layer 23, which is disposed on the topmost layer of the composite layer 20, is higher, which is beneficial to accelerating the transmission rate of lithium ions, allowing more lithium ions to enter the second composite layer 22 for ion exchange with the positive electrode active material, and at the same time, it is beneficial to reduce the lithium ion concentration on the surface of the positive electrode plate, preventing lithium ions from aggregating or precipitating on the surface of the positive electrode plate, and thus improving the safety of the battery. In addition, the content of the second fast ion conductor disposed on the topmost layer of the composite layer 20 is higher than the content of the first fast ion conductor in the middle layer of the composite layer 20, so that lithium ions can form a concentration gradient difference between the topmost layer and the middle layer of the composite layer 20, which is beneficial to the migration of lithium ions into the second composite layer 22, increasing the lithium ion concentration in the second composite layer 22, and thus improving the energy density of the battery.

[0028] Based on the above embodiment, as an optional embodiment, the second composite layer 22 includes, by weight, 80 to 98 parts of the positive electrode active material, 1 to 19 parts of the first fast ion conductor, 1 to 19 parts of the second conductive agent, and 0.5 to 19 parts of the second binder. As a preferred embodiment, the second composite layer 22 includes, by weight, 94 to 96 parts of the positive electrode active material, 1 to 2 parts of the first fast ion conductor, 2 parts of the second conductive agent, and 1 to 2 parts of the second binder. For example, the mass ratio of the positive electrode active material, the first fast ion conductor, the second conductive agent, and the second binder is 94:2:2:2, 95:2:2:1, or 96:1:2:1. Therefore, the proportion of positive electrode active material in the second composite layer 22 is the highest, which increases the loading amount of the positive electrode active material and is beneficial to improving the energy density of the battery. The mass of the first fast ion conductor and the second conductive agent is within the above range, which is beneficial to improving the ionic conductivity and electronic conductivity. The mass of the second binder is within the above range, which is beneficial to improving the bonding strength between the second composite layer and the first composite layer and the third composite layer, and improving the overall structural stability of the composite layer 20.

[0029] Based on the above embodiment, as an optional embodiment, the third composite layer 23 includes, by weight, 5 to 40 parts of the second fast ion conductor, 70 to 95 parts of the third conductive agent, and 2 to 5 parts of the third binder. As a preferred embodiment, the third composite layer 23 includes, by weight, 10 to 20 parts of the second fast ion conductor, 75 to 85 parts of the third conductive agent, and 5 parts of the third binder. For example, the mass ratio of the second fast ion conductor, the third conductive agent, and the third binder is 10:85:5, 15:80:5, or 20:75:5. As a result, the content of the third conductive agent and the second fast ion conductor in the third composite layer 23 is relatively high, and the third composite layer 23 is close to the diaphragm and in direct contact with the electrolyte, which is beneficial to improving the ionic conductivity and electronic conductivity, and can effectively improve the lithium ion transmission performance of the positive electrode sheet.

[0030] Based on the above embodiment, as an optional implementation, in the first composite layer 21, the mass ratio of the first conductive agent to the first binder is 30:70 to 99:1, wherein the mass of the first conductive agent may account for 30% to 99% of the total mass of the first composite layer 21, and the mass of the first binder may account for 1% to 70% of the total mass of the first composite layer 21. As a preferred implementation, the mass ratio of the first conductive agent to the first binder is 70:30 to 95:5, for example, the mass ratio of the first conductive agent to the first binder is 30:70, 40:60, 50:50, 60:40, or 70:30. Therefore, the content of the first binder in the first composite layer 21 is relatively high, which can improve the bonding strength between the first composite layer 21 and the positive electrode current collector 10, make the composite layer 20 more firmly bonded to the positive electrode current collector 10, and improve the structural strength of the positive electrode sheet. At the same time, the content of the first conductive agent is within the above range, which can further promote the electron transmission between the composite layer 20 and the positive electrode current collector 10 and reduce the polarization of the positive electrode sheet.

[0031] Based on the above embodiment, as an optional implementation, in the composite layer 20, the thickness of the second composite layer 22 is greater than the thickness of the third composite layer 23, and the thickness of the third composite layer 23 is greater than the thickness of the first composite layer 21. As a result, the second composite layer 22 in the composite layer 20 has the largest thickness, which can increase the loading amount of the positive electrode active material and is beneficial to improving the specific capacity of the battery. The first composite layer 21 has the smallest thickness, which is beneficial to improving the energy density of the battery on the one hand, and on the other hand, the first composite layer 21 with a smaller thickness can be more tightly bonded to the positive electrode current collector 10, which is beneficial to improving the structural strength of the positive electrode sheet. The thickness of the third composite layer 23 is between the first composite layer 21 and the second composite layer 22, which is beneficial to accelerating the transmission rate of lithium ions and preventing lithium ions from aggregating or precipitating on the surface of the positive electrode sheet.

[0032] Based on the above embodiment, as an optional implementation, the thickness of the first composite layer 21 is less than or equal to 10 μm, for example, the thickness of the first composite layer 21 is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, or 8 μm. As a preferred implementation, the thickness of the first composite layer 21 ranges from 2 μm to 5 μm, for example, the thickness of the first composite layer 21 is 2 μm, 3 μm, 4 μm, or 5 μm.

[0033] Based on the above embodiment, as an optional implementation, the thickness of the second composite layer 22 is greater than or equal to 30 μm, for example, the thickness of the second composite layer 22 is 30 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, or 1000 μm. As a preferred implementation, the thickness of the second composite layer 22 ranges from 300 μm to 1000 μm, for example, the thickness of the second composite layer 22 is 300 μm, 500 μm, 700 μm, 800 μm, or 1000 μm.

[0034] Based on the above embodiment, as an optional implementation, the thickness of the third composite layer 23 is less than or equal to 20 μm. For example, the thickness of the third composite layer 22 is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, or 8 μm. As a preferred implementation, the thickness of the third composite layer 23 ranges from 2 μm to 10 μm. For example, the thickness of the third composite layer 23 is 3 μm, 4 μm, 5 μm, 7 μm, or 10 μm.

[0035] Based on the above embodiment, as an optional implementation, the thickness of the composite layer 20 is greater than or equal to 30 μm, for example, the thickness of the composite layer 20 is 30 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, or 1000 μm. As a preferred implementation, the thickness of the composite layer 20 ranges from 300 μm to 1000 μm, for example, the thickness of the composite layer 20 is 300 μm, 400 μm, 600 μm, 800 μm, or 1000 μm.

[0036] Based on the above embodiment, as an optional implementation, the compaction density of the composite layer 20 is 3.2 g / cm 3 Up to 4.3g / cm 3 , for example: 3.2g / cm 3 , 3.5g / cm 3 、3.8g / cm 3 , 4.0g / cm 3 or 4.3g / cm 3Therefore, the compaction density of the composite layer 20 is within the above range, which can ensure a large contact area between the positive electrode active materials without blocking the ion transfer channel, ensuring good electron conductivity and ion mobility during high current discharge, which is beneficial to improving the rate performance of the battery.

[0037] Based on the above embodiment, as an optional implementation manner, the first conductive agent, the second conductive agent and the third conductive agent are the same or different, and are independently selected from one or a combination of conductive carbon black (SP), Ketjen black, carbon fiber (VGCF), carbon nanotubes (CNT), graphene and reduced graphene oxide (rGO).

[0038] Based on the above embodiment, as an optional implementation, the first binder, the second binder and the third binder are the same or different, and are independently selected from one or a combination of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF) and polyacrylic acid (PAA).

[0039] Based on the above embodiment, as an optional embodiment, the positive electrode active material is selected from lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), nickel cobalt manganese ternary material (LiNi x Co y Mn z O2, where x+y+z=1), nickel-cobalt-aluminum ternary materials (LiNi x Co y Al z O2, wherein x+y+z=1) and one or more combinations of lithium-rich manganese-based materials. Thus, the positive electrode active material is rich in lithium, which is beneficial to improving the energy density of the battery.

[0040] Based on the above embodiment, as an optional implementation, the positive electrode current collector 10 can be selected from one or a combination of metal foils such as aluminum foil, copper foil, nickel foil, gold foil and platinum foil. The positive electrode current collector 10 can also be selected from one or a combination of composite aluminum foil, carbon-coated aluminum foil and electroplated aluminum foil.

[0041] A second aspect of an embodiment of the present application provides a method for preparing a positive electrode sheet, which is used to prepare the positive electrode sheet of the first aspect.

[0042] Figure 2 The process flow chart of preparing the positive electrode sheet in the embodiment of the present invention is shown in FIG. Figure 2 As shown, the preparation method of the positive electrode sheet includes the following steps:

[0043] Step S210 : Mix the first conductive agent and the first adhesive and perform fiberization treatment to obtain a first composite layer 21 .

[0044] Specifically, the first conductive agent and the first binder are mixed at a first rotation speed, and after being evenly mixed, are sent to a jet mill for fiberization treatment, and rolled to a first preset thickness to obtain the first composite layer 21, wherein the first preset thickness is less than or equal to 10 μm.

[0045] Based on the above embodiment, as an optional implementation, the first rotational speed is 500r / min to 1000r / min, and the mixing time is 30min to 300min. Therefore, mixing at this rotational speed is conducive to uniform dispersion of the first conductive agent and the first adhesive, and allows the two to be fully mixed.

[0046] Based on the above embodiment, as an optional implementation, the temperature of the air flow mill for fiberization treatment is 90°C to 200°C, the fiberization treatment time is 2h to 10h, and the rolling temperature is 150°C to 300°C.

[0047] Step S220 , mixing the positive electrode active material, the first fast ion conductor and the second conductive agent to obtain a first mixture, adding the second binder to the first mixture to obtain a second mixture, and performing fiberization treatment on the second mixture to obtain a second composite layer 22 .

[0048] Specifically, the positive electrode active material, the first fast ion conductor and the second conductive agent are mixed at a first rotational speed, and after being mixed evenly, a first mixture is obtained. The second binder is added to the first mixture, and the mixture is mixed at a second rotational speed to obtain a second mixture. The second mixture is sent to a jet mill for fiberization treatment and rolled to a second preset thickness to obtain a second composite layer 22, wherein the second preset thickness is greater than or equal to 30 μm.

[0049] Based on the above embodiment, as an optional implementation, the first speed is greater than the second speed, the first speed is 500 r / min to 1000 r / min, and the second speed is 100 r / min to 500 r / min. The positive electrode active material, the first fast ion conductor, and the second conductive agent are mixed at the first speed for 30 to 300 minutes, and the first mixture and the second binder are mixed at the second speed for 10 to 60 minutes. Thus, the first speed is greater than the second speed, which can ensure that the positive electrode active material, the first fast ion conductor, and the second conductive agent are evenly dispersed and fully mixed. After the second binder is added, the speed is reduced to prevent the second binder from prematurely entering fiberization, causing agglomeration between the powders, affecting the uniformity of the second mixture, and thus affecting the performance of the second composite layer 22.

[0050] The temperature, time and rolling temperature of the fiberized material fed into the air jet mill for fiberization in step S220 are the same as those in step S210 and will not be described in detail here.

[0051] Step S230 : Mix the second fast ion conductor and the third conductive agent to obtain a third mixture, add a third binder to the third mixture to obtain a fourth mixture, and perform fiberization on the fourth mixture to obtain a third composite layer 23 .

[0052] Specifically, the second fast ion conductor and the third conductive agent are mixed at a first rotational speed, and after mixing evenly, a third mixture is obtained. A third binder is added to the third mixture, and the mixture is mixed at a second rotational speed to obtain a fourth mixture. The fourth mixture is sent to a jet mill for fiberization treatment and rolled to a third preset thickness to obtain a third composite layer 23, wherein the third preset thickness is less than or equal to 20 μm.

[0053] Based on the above embodiment, as an optional implementation, the first speed is greater than the second speed, the first speed is 500 r / min to 1000 r / min, and the second speed is 100 r / min to 500 r / min. The second fast ion conductor and the third conductive agent are mixed at the first speed for 30 to 300 minutes, and the third mixture and the third binder are mixed at the second speed for 10 to 60 minutes. Thus, the first speed being greater than the second speed ensures that the second fast ion conductor and the third conductive agent are evenly dispersed and fully mixed. Reducing the speed after adding the third binder can prevent the third binder from prematurely fiberizing, causing powder agglomeration and affecting the uniformity of the fourth mixture, thereby affecting the performance of the third composite layer 23.

[0054] The temperature, time and rolling temperature of the fiberized material fed into the air jet mill for fiberization in step S230 are the same as those in step S210 and will not be described in detail here.

[0055] Step S240 , stacking the first composite layer 21 , the second composite layer 22 and the third composite layer 23 in sequence, and rolling them to obtain the composite layer 20 .

[0056] Specifically, the first composite layer 21, the second composite layer 22, and the third composite layer 23 are stacked in sequence and then roll-pressed to produce the composite layer 20. Thus, the first composite layer 21, the second composite layer 22, and the third composite layer 23 are stacked in sequence and then roll-pressed, which enables shallow diffusion on the contact surfaces of the composite layers. This not only helps to improve the bonding strength between the composite layers and the structural strength of the composite layer 20, but also improves the ion and electron transmission efficiency between the composite layers.

[0057] Based on the above embodiment, as an optional implementation manner, the rolling temperature is 150°C to 300°C.

[0058] Step S250 : disposing the composite layer 20 on at least one side of the positive electrode current collector 10 , with the first composite layer 21 in contact with the positive electrode current collector 10 , and performing roll pressing to obtain a positive electrode sheet.

[0059] Based on the above embodiment, as an optional implementation manner, the rolling temperature is 150°C to 300°C.

[0060] The method for preparing the positive electrode sheet provided in this embodiment, by sequentially preparing the first composite layer, the second composite layer, and the third composite layer, can avoid the mutual influence of the composite layers during the preparation process, and can ensure the uniformity of the mixing of the various mixed materials, thereby improving the performance of each composite layer. After each composite layer is prepared separately, the first composite layer, the second composite layer, and the third composite layer are composited together, which can cause shallow diffusion on the contact surface of each composite layer, which is beneficial to improving the bonding strength between each composite layer, and is beneficial to improving the structural strength of the composite layer and the ion and electron transmission efficiency between each composite layer. The preparation method of this embodiment is conducive to further improving the electrochemical performance of the battery. The preparation method adopts a dry preparation process, avoids the use of organic solvents, is environmentally friendly, can reduce production costs, and is suitable for industrial mass production.

[0061] The third aspect of the embodiment of the present application also provides a battery, including a battery cell, the battery cell includes a positive electrode sheet, a negative electrode sheet and a separator arranged between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet, the negative electrode sheet and the separator are stacked or wound to form a battery cell, the positive electrode sheet is the positive electrode sheet described in the first aspect, and the battery also includes an electrolyte and a shell, and the battery cell and the electrolyte are encapsulated in the shell.

[0062] In this embodiment, the negative electrode plate may be a negative electrode plate of conventional structure, that is, only one negative electrode active material layer is provided on the surface of the negative electrode collector of the negative electrode plate.

[0063] In the battery, the electrolyte can be a liquid electrolyte, which can include lithium salts and non-aqueous organic solvents. There is no specific limitation on the type of electrolyte, as long as it can ensure the normal transmission of metal ions. For example, the electrolyte can be 1 mol / L LiPF6 and non-aqueous organic solvents such as ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC) or fluoroethylene carbonate (FEC).

[0064] In the battery, the type of the separator is not specifically limited and can be selected according to actual needs. Specifically, the separator can be selected from polyethylene film, polypropylene film, polyvinylidene fluoride film and multilayer composite films thereof.

[0065] In order to further explain the present invention in detail, the present invention will be further described below with reference to specific examples. Unless otherwise specified, the experimental methods used in the examples of the present invention are conventional methods; unless otherwise specified, the materials, reagents, etc. used in the examples of the present invention are all purchased from the market.

[0066] Example 1

[0067] This embodiment provides a method for preparing a positive electrode sheet, comprising the following steps:

[0068] (1) Preparing a first composite layer: Weigh a first conductive agent and a first binder in a mass ratio of 95:5, wherein the first conductive agent is composed of SP, CNT, and graphene, and the mass ratio of SP, CNT, and graphene is 90:5:5, and the first binder is PTFE. Place the first conductive agent and the first binder in a high-speed mixer and mix them to obtain a fluffy mixed powder. The fluffy mixed powder is transferred to a multi-stage hot roller pressing device via a powder metering and conveying device. The roller pressing temperature is set to 200°C. After multiple hot roller pressings, the device is rolled up to obtain a self-supporting first composite layer. The thickness of the first composite layer is 2.5 μm to 3.5 μm.

[0069] (2) Preparation of the second composite layer: The positive electrode active material, the first fast ion conductor, the second conductive agent, and the second binder are weighed in a mass ratio of 95:1:3.5:0.5, wherein the positive electrode active material is LFP, the first fast ion conductor is LiAlSiO4, the second conductive agent is composed of SP and CNT, the mass ratio of SP to CNT is 8:1, and the second binder is PTFE. The positive electrode active material, the first fast ion conductor, and the second conductive agent are placed in a high-speed mixer and mixed at 700 r / min for 120 min to obtain a first mixture. The second binder is added to the first mixture and mixed at 300 r / min for 60 min to obtain a fluffy second mixture. The second mixture is transferred to a multi-stage hot roller pressing device through a powder metering and conveying device. The roller pressing temperature is set to 200°C. After multiple hot roller pressings, the mixture is rolled up to obtain a self-supporting second composite layer. The thickness of the second composite layer is 499 μm to 501 μm.

[0070] (3) Preparation of the third composite layer: weigh a second fast ion conductor, a third conductive agent, and a third binder in a mass ratio of 15:80:5, wherein the second fast ion conductor is LiAlSiO4, the second conductive agent is composed of SP and CNT, the mass ratio of SP to CNT is 8:1, and the third binder is PTFE. The second fast ion conductor and the third conductive agent are placed in a high-speed mixer and mixed at 700 r / min for 120 minutes to obtain a third mixture. The third binder is added to the third mixture and mixed at 300 r / min for 60 minutes to obtain a fluffy fourth mixture. The fourth mixture is transferred to a multi-stage hot roller pressing device through a powder metering and conveying device. The roller pressing temperature is set to 200°C. After multiple hot roller pressings, the mixture is rolled up to obtain a self-supporting third composite layer. The thickness of the third composite layer is 2.5 μm to 3.5 μm.

[0071] (4) Preparation of composite layer: The first composite layer, the second composite layer and the third composite layer are stacked in sequence from bottom to top, and transferred to a multi-stage hot rolling device. The rolling temperature is set to 200°C. After multiple hot rolling processes, the layers are rolled up to obtain a self-supporting composite layer.

[0072] (5) Preparation of positive electrode sheet: The composite layer is arranged on one side surface of the positive electrode current collector, with the first composite layer in contact with the positive electrode current collector, and is transferred to a multi-stage hot rolling device. The rolling temperature is set to 200°C. After multiple hot rolling processes, the composite layer is rolled up to obtain a positive electrode sheet.

[0073] Example 2

[0074] This embodiment provides a method for preparing a positive electrode sheet. The preparation process of the positive electrode sheet is the same as that of Example 1, except that:

[0075] Preparation of the first composite layer: A first conductive agent and a first binder are weighed in a mass ratio of 95:5. The first conductive agent comprises SP, CNT, and graphene in a mass ratio of 90:5:5. The first binder is PTFE. The first conductive agent and the first binder are mixed in a high-speed mixer to produce a fluffy mixed powder. The fluffy mixed powder is transferred via a powder metering and conveying device to a multi-stage hot roller press at 200°C. After multiple hot roller presses, the mixture is rolled up to obtain a self-supporting first composite layer having a thickness of 9.5 to 10.5 μm.

[0076] Example 3

[0077] This embodiment provides a method for preparing a positive electrode sheet. The preparation process of the positive electrode sheet is the same as that of Example 1, except that:

[0078] Preparation of the second composite layer: The positive electrode active material, the first fast ion conductor, the second conductive agent, and the second binder were weighed in a mass ratio of 95:1:3.5:0.5, wherein the positive electrode active material was LFP, the first fast ion conductor was LiAlSiO4, the second conductive agent was composed of SP and CNT in a mass ratio of 8:1, and the second binder was PTFE. The positive electrode active material, the first fast ion conductor, and the second conductive agent were placed in a high-speed mixer and mixed at 700 rpm for 120 minutes to produce a first mixture. The second binder was added to the first mixture and mixed at 300 rpm for 60 minutes to produce a fluffy second mixture. The second mixture was transferred to a multi-stage hot roller press via a powder metering and conveying device at a rolling temperature of 200°C. After multiple hot roller presses, the mixture was rolled up to obtain a self-supporting second composite layer. The thickness of the second composite layer was 599 μm to 601 μm.

[0079] Example 4

[0080] This embodiment provides a method for preparing a positive electrode sheet. The preparation process of the positive electrode sheet is the same as that of Example 1, except that:

[0081] Preparation of the third composite layer: A second fast ion conductor, a third conductive agent, and a third binder are weighed in a mass ratio of 15:80:5, wherein the second fast ion conductor is LiAlSiO4, the second conductive agent is composed of SP and CNT in a mass ratio of 8:1, and the third binder is PTFE. The second fast ion conductor and the third conductive agent are placed in a high-speed mixer and mixed at 700 rpm for 120 minutes to produce a third mixture. The third binder is added to the third mixture and mixed at 300 rpm for 60 minutes to produce a fluffy fourth mixture. The fourth mixture is transferred via a powder metering and conveying device to a multi-stage hot roller press at 200°C. After multiple hot roller presses, the mixture is rolled up to produce a self-supporting third composite layer having a thickness of 4.5 μm to 5.5 μm.

[0082] Comparative Example 1

[0083] This comparative example provides a method for preparing a positive electrode sheet. The preparation process of the positive electrode sheet is the same as that of Example 1, except that:

[0084] The positive electrode plate of this comparative example does not include the first composite layer. The composite layer only includes the second composite layer and the third composite layer. The second composite layer is in direct contact with the positive current collector. That is, the second composite layer is arranged on the positive current collector, and the third composite layer is arranged on the second composite layer.

[0085] Comparative Example 2

[0086] This comparative example provides a method for preparing a positive electrode sheet. The preparation process of the positive electrode sheet is the same as that of Example 1, except that:

[0087] The positive electrode plate of this comparative example does not include the third composite layer. The composite layer only includes the first composite layer and the second composite layer. The first composite layer is in direct contact with the positive current collector. That is, the first composite layer is arranged on the positive current collector, and the second composite layer is arranged on the first composite layer.

[0088] Comparative Example 3

[0089] This comparative example provides a method for preparing a positive electrode sheet. The preparation process of the positive electrode sheet is the same as that of Example 1, except that:

[0090] After the first composite layer, the second composite layer and the third composite layer are prepared, the first composite layer, the second composite layer and the third composite layer are not rolled to prepare the composite layer. That is, after the first composite layer, the second composite layer and the third composite layer are prepared, the first composite layer, the second composite layer and the third composite layer are directly arranged in sequence from bottom to top on the surface of the positive electrode current collector, and the three composite layers are not pre-compounded into one.

[0091] Comparative Example 4

[0092] This comparative example provides a method for preparing a positive electrode sheet. The preparation process of the positive electrode sheet is as follows:

[0093] The positive electrode active material, first fast ion conductor, second conductive agent, and second binder were weighed in a mass ratio of 95:1:3.5:0.5. The positive electrode active material was LFP, the first fast ion conductor was LiAlSiO₄, the second conductive agent consisted of SP and CNT in a mass ratio of 8:1, and the second binder was PTFE. The positive electrode active material, first fast ion conductor, and second conductive agent were placed in a high-speed mixer and mixed at 700 rpm for 120 minutes. The second binder was then added and mixed at 300 rpm for 60 minutes to produce a fluffy mixed powder. The mixed powder was then transferred via a powder metering and conveying device to a multi-stage hot roller press at 200°C. After multiple hot roller presses, the mixture was rolled up to obtain a self-supporting composite layer. This composite layer was directly applied to one side of the positive electrode current collector and transferred to a multi-stage hot roller press at 200°C. After multiple hot roller presses, the mixture was rolled up to obtain a positive electrode sheet.

[0094] The positive electrode sheets, negative electrode sheets and separators prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were assembled into batteries, wherein the negative electrode sheets can be prepared by the following method:

[0095] The negative electrode active material, styrene diene rubber (SBR), sodium hydroxymethyl cellulose and conductive carbon black were uniformly mixed in a weight ratio of 94%:3%:2%:1%, the mixture was dispersed in water, and a negative electrode slurry was obtained by double planetary mixing. The negative electrode slurry was coated on a copper current collector, followed by roll pressing and drying to obtain a negative electrode sheet.

[0096] The positive electrode sheets, separators and negative electrode sheets prepared in Examples 1 to 4 and Comparative Examples 1 to 4 are stacked in sequence to prepare laminated battery cells, which are then packaged in aluminum-plastic film shells. After packaging, the packaged battery cells are hot-pressed to prepare soft-pack battery cells.

[0097] The performance of the soft-pack batteries prepared using the positive electrode sheets of Examples 1 to 4 and Comparative Examples 1 to 4 was tested:

[0098] The capacity retention rate of each soft-pack battery cell after 500 cycles was measured under the following test conditions: 1C charge and 1C discharge conditions, the charge and discharge temperature was 25°C, and the voltage range was 2.5V to 3.85V. The capacity ratio of the discharge capacity at 0.2C at room temperature of 25°C was recorded as the room temperature cycle retention rate.

[0099] Test the capacity retention rate of each soft-pack battery cell after 50 charge and discharge cycles at 0.2C at 45°C. Test conditions: the capacity is compared with the capacity at room temperature of 25°C and 0.2C discharge, and the high temperature retention rate is recorded.

[0100] Test the 2.0C rate discharge capacity of each soft-pack battery cell at room temperature. Test conditions: take the 0.2C capacity as 100% initial comparative capacity retention rate, recorded as the rate retention rate;

[0101] The EIS internal resistance value of each soft-pack battery cell at room temperature and 50% SOC is tested and recorded as the impedance value.

[0102] The performance test results of each embodiment and comparative example are shown in Table 1.

[0103] Table 1

[0104]

[0105] It can be seen from Examples 1 to 4 and Comparative Example 1 in Table 1 that when the composite layer lacks the first composite layer, the high-temperature cycle retention rate, normal temperature cycle retention rate, and rate retention rate of the soft-pack battery are significantly lower than those of the soft-pack battery in Examples 1 to 4, and the impedance value is significantly higher than that of the soft-pack battery in Examples 1 to 4, which shows that providing the first composite layer in the positive electrode sheet is beneficial to reducing resistance and can significantly improve the electrochemical performance of the lithium battery. It can be seen from Examples 1 to 4 and Comparative Example 2 in Table 1 that when the composite layer lacks the third composite layer, the high-temperature cycle retention rate, normal temperature cycle retention rate, and rate retention rate of the soft-pack battery are significantly lower than those of the soft-pack battery in Examples 1 to 4, and the impedance value is significantly higher than that of the soft-pack battery in Examples 4, which shows that providing the third composite layer in the positive electrode sheet is beneficial to reducing resistance and can significantly improve the electrochemical performance of the lithium battery. It can be seen from Examples 1 to 4 and Comparative Example 3 in Table 1 that when the first composite layer, the second composite layer, and the third composite layer are not pre-rolled to form a composite layer, the high-temperature cycle retention rate, the room-temperature cycle retention rate, and the rate retention rate of the soft-pack battery are significantly lower than those of the soft-pack battery in Examples 1 to 4, and the impedance value is significantly higher than that of the soft-pack battery in Examples 1 to 4. This shows that the first composite layer, the second composite layer, and the third composite layer are pre-rolled to form a composite layer, and then provided on the positive electrode current collector, which can bond each composite layer more tightly, thereby reducing the interface effect of the positive electrode sheet as a whole and improving the electrochemical performance of the positive electrode sheet. It can be seen from Examples 1 to 4 and Comparative Example 4 in Table 1 that after the layers in the composite layer are prepared in layers and then composited into one, compared with a single composite layer, the high-temperature cycle retention rate, room-temperature cycle retention rate, and rate retention rate of the soft-pack battery can be significantly improved, and the impedance value of the soft-pack battery can be reduced.

[0106] Although the present disclosure is disclosed as above, the protection scope of the present disclosure is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present disclosure, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A positive electrode plate, characterized in that: include: A positive electrode current collector and a composite layer disposed on at least one side of the positive electrode current collector; The composite layer includes a first composite layer, a second composite layer and a third composite layer sequentially arranged along the thickness direction of the positive electrode sheet, wherein the first composite layer is arranged on the surface of the positive electrode current collector; The first composite layer includes a first conductive agent and a first binder, the second composite layer includes a positive electrode active material, a second conductive agent, a second binder and a first fast ion conductor, and the third composite layer includes a third conductive agent, a third binder and a second fast ion conductor.

2. The positive electrode sheet according to claim 1, characterized in that: The content of the first fast ion conductor in the second composite layer is lower than the content of the second fast ion conductor in the third composite layer.

3. The positive electrode sheet according to claim 1, characterized in that: In the first composite layer, the mass ratio of the first conductive agent to the first binder is 30:70 to 99:

1.

4. The positive electrode sheet according to claim 1, characterized in that: In parts by weight, the second composite layer includes: 80 to 98 parts of the positive electrode active material, 1 to 19 parts of the first fast ion conductor, 1 to 19 parts of the second conductive agent, and 0.5 to 19 parts of the second binder.

5. The positive electrode sheet according to claim 1, characterized in that: In parts by weight, the third composite layer includes: 5 to 40 parts of the second fast ion conductor, 70 to 95 parts of the third conductive agent, and 2 to 5 parts of the third binder.

6. The positive electrode sheet according to claim 1, characterized in that: The thickness of the second composite layer is greater than that of the third composite layer, and the thickness of the third composite layer is greater than that of the first composite layer.

7. The positive electrode sheet according to claim 1, characterized in that: The thickness of the second composite layer is greater than or equal to 30 μm, the thickness of the third composite layer is less than or equal to 20 μm, and the thickness of the first composite layer is less than or equal to 10 μm.

8. The positive electrode sheet according to claim 1, characterized in that: The first fast ion conductor is selected from Li3SBF4, LiAlSiO4, LiTaSiO5, Li 10 Si2PO 10 and Li2P3SiO8 or a combination of several thereof; And / or, the second fast ion conductor is selected from Li3SBF4, LiAlSiO4, LiTaSiO5, Li 10 Si2PO 10 and Li2P3SiO8 or a combination of any of the above.

9. A method for preparing a positive electrode sheet, characterized in that: For preparing the positive electrode sheet according to any one of claims 1 to 8, the preparation method comprises the following steps: The first conductive agent and the first binder are mixed and then subjected to a fiberization treatment to prepare a first composite layer; Mixing a positive electrode active material, a first fast ion conductor, and a second conductive agent to prepare a first mixture, adding a second binder to the first mixture to prepare a second mixture, and performing a fiberization treatment on the second mixture to prepare a second composite layer; mixing the second fast ion conductor and the third conductive agent to obtain a third mixture, adding a third binder to the third mixture to obtain a fourth mixture, and performing a fiberization treatment on the fourth mixture to obtain a third composite layer; The first composite layer, the second composite layer and the third composite layer are stacked in sequence and roll-pressed to obtain a composite layer; The composite layer is arranged on at least one side surface of a positive electrode current collector, the first composite layer is in contact with the positive electrode current collector, and roll pressing is performed to obtain a positive electrode sheet.

10. A battery, characterized in that: The invention comprises the positive electrode sheet according to any one of claims 1 to 8, or the positive electrode sheet prepared by the method for preparing the positive electrode sheet according to claim 9.

Citation Information

Cited By

  • Positive pole piece, lithium ion battery comprising positive pole piece, and electronic device comprising positive pole piece

    CN122067976A

  • A positive electrode sheet, and a lithium ion battery and an electronic device comprising the same

    CN122067976B